EVALUASI SIMPANG UTAMA KORIDOR SELATAN KOTA SEMARANG STUDI KASUS SIMPANG BANYUMANIK - Nugroho, Untoro (Jurnal Teknik Sipil dan Perencanaan, 2011)
Abstrak: The position of SemarangÃÂ  reviewedÃÂ  in national andÃÂ  regional scaleÃÂ  is very strategic,ÃÂ  theimpacts ofÃÂ  traffic growth are sustainedÃÂ  locally and are quiteÃÂ  large. That growthÃÂ  trafficÃÂ  flows should be assessedÃÂ  continuouslyÃÂ  so asÃÂ  to avoid negativeÃÂ  impacts. The pattern ofÃÂ  trafficÃÂ  flowsÃÂ  in aÃÂ  road section can be seen from the intersection arrangement pattern that is on the segment. Parameters studied include:ÃÂ  the number of vehicles out of each arm, current conditions andÃÂ  time of the signal. ThisÃÂ  analysisÃÂ  includes:ÃÂ  theÃÂ  basicÃÂ  saturationÃÂ  flow,ÃÂ  trafficÃÂ  flow,ÃÂ  cycleÃÂ  time,ÃÂ  greenÃÂ  time,ÃÂ  capacity, degree of saturation and traffic behavior. From the results of research on the signalized intersection atÃÂ  theÃÂ  intersection Banyumanik, obtained byÃÂ  the basic saturationÃÂ  flow onÃÂ  the northern approach of 5310 pcu/h, east of 3060 pcu/h, south of 4740 pcu/h. Saturation flow rate on the northern approach of 4117 pcu/h, east of 2100 pcu/h, south of 4064 pcu/h. Comparison ofÃÂ  the currentÃÂ  intersection of 0.857. greenÃÂ  time of 161 seconds. Capacity onÃÂ  the northern approach of 2474 pcu/h, east of 681 pcu/h, south of 2442 pcu/h. Degree of Saturation onÃÂ  the northern approach of 0.7284 pcu/h, east .9261 pcu/h, south of 0.9261 pcu/h. The number of queues on the approach north of 58 pcu, pcu 32 east, south 96.3 pcu. Long queues at the northern approach of 180 meters, 178 meters east, south 294ÃÂ  yards.ÃÂ  TheÃÂ  numberÃÂ  ofÃÂ  stoppedÃÂ  vehiclesÃÂ  throughoutÃÂ  intersectionsÃÂ  0.80ÃÂ  stop/pcu.Tundaan crossingÃÂ  byÃÂ  anÃÂ  averageÃÂ  ofÃÂ  40.76ÃÂ  sec/pcu.ÃÂ  TheÃÂ  amountÃÂ  ofÃÂ  capacityÃÂ  andÃÂ  degreeÃÂ  ofÃÂ  saturationÃÂ  is almost past the recommended limit, so that wide approach needs to change. Keywords:ÃÂ  evaluation, optimization, intersection, Banyumanik ÃÂ  Abstrak:ÃÂ  PosisiÃÂ  kotaÃÂ  SemarangÃÂ  ditinjauÃÂ  dalamÃÂ  skalaÃÂ  nasional maupunÃÂ  regionalÃÂ  sangatÃÂ  strategis akan menimbulkanÃÂ  dampakÃÂ  pertumbuhanÃÂ  laluÃÂ  lintasÃÂ  yangÃÂ  bersifatÃÂ  lokal maupunÃÂ  menerusÃÂ  yang cukup besar. PertumbuhanÃÂ  laluÃÂ  lintas yang cukup besar menghasilkan arusÃÂ  laluÃÂ  lintas yang harus dikajiÃÂ  terusÃÂ  menerusÃÂ  sehinggaÃÂ  tidakÃÂ  menimbulkanÃÂ  dampakÃÂ  negatif.ÃÂ  ArusÃÂ  laluÃÂ  lintasÃÂ  yangÃÂ  cukup besarÃÂ  tanpaÃÂ  disertaiÃÂ  pengaturanÃÂ  polaÃÂ  laluÃÂ  lintasÃÂ  yangÃÂ  sesuaiÃÂ  akan menyebabkanÃÂ  tundaanÃÂ  yang cukupÃÂ  lama dan antrian yang cukup panjang. Pola arusÃÂ  laluÃÂ  lintas suatu ruasÃÂ  jalan dapat kitaÃÂ  lihat dariÃÂ  polaÃÂ  pengaturanÃÂ  simpangÃÂ  yangÃÂ  beradaÃÂ  padaÃÂ  ruasÃÂ  tersebut.ÃÂ  ParameterÃÂ  yangÃÂ  diteliti eliputi jumlahÃÂ  kendaraanÃÂ  yangÃÂ  keluarÃÂ  dari masing.masingÃÂ  lengan,ÃÂ  kondisiÃÂ  saatÃÂ  iniÃÂ  dan waktuÃÂ  sinyalnya. Analisis ini meliputi : arus jenuh dasar, arus lalu lintas, waktu siklus, waktu hijau, kapasitas, derajat kejenuhan dan perilakuÃÂ  laluÃÂ  lintas. Dari hasil penelitian pada simpang bersinyal di persimpangan banyumanik, diperoleh arusÃÂ  jenuh dasar pada pendekat utara sebesar 5310 smp/jam,ÃÂ  timur 3060 smp/jam,ÃÂ  selatanÃÂ  4740ÃÂ  smp/jam.ÃÂ  NilaiÃÂ  arusÃÂ  jenuhÃÂ  padaÃÂ  pendekatÃÂ  utaraÃÂ  sebesarÃÂ  4117 smp/jam, timurÃÂ  2100ÃÂ  smp/jam,ÃÂ  selatanÃÂ  4064ÃÂ  smp/jam.ÃÂ  PerbandinganÃÂ  arusÃÂ  simpangÃÂ  sebesarÃÂ  0,857.ÃÂ  waktu hijauÃÂ  sebesarÃÂ  161ÃÂ  detik.ÃÂ  KapasitasÃÂ  padaÃÂ  pendekatÃÂ  utaraÃÂ  sebesarÃÂ  2474ÃÂ  smp/jam,ÃÂ  timurÃÂ  681 smp/jam, selatan 2442 smp/jam. Derajat Kejenuhan pada pendekat utara sebesar 0,7284 smp/jam, timur 0,9261 smp/jam, selatan 0,9261 smp/jam. Jumlah antrian pada pendekat utara sebesar 58 smp,ÃÂ  timur 32 smp, selatan 96,3 smp. Panjang antrian pada pendekat utara sebesar 180 meter, timurÃÂ  178ÃÂ  meter,ÃÂ  selatanÃÂ  294ÃÂ  meter.ÃÂ  JumlahÃÂ  kendaraanÃÂ  terhentiÃÂ  seluruhÃÂ  simpangÃÂ  0,80 stop/smp.Tundaan persimpangan rata.rata sebesar 40,76 det/smp. Besarnya kapasitas dan derajat kejenuhan hampir melewati batas yang disarankan, sehingga perlu perubahan lebar pendekat. Kata kunci : evaluasi, optimalisasi, simpang, Banyumanik